How Excessive Stage Time Reduction in NPD Negatively Impacts Market Value. Issue 5 (13th October 2015) - Bendoly, Elliot; Chao, Raul O.
Abstract : We empirically investigate how time reductions in particular product development stages impact market value. Using longitudinal project data from 107 firms, we compare stage times prior to and following investments in new product development process changes. Our analysis reveals a predominance of focus on time reduction in the late stages of product development. We also find support for the existence of an inverted‐U relationship between market performance and time reductions for some of these stages: beta testing and technical implementation. Therefore, while time reductions can improve time to market, we observe a clear limit to the benefits associated with stage time reductions at particular stages. We also investigate the role of strategic contextual factors such as the extent to which a firm's patented innovations rely upon a variety, as opposed to a limited range, of diverse technology classes. The extent of this technology‐span impacts optimal stage time reductions. We perform an in‐depth post hoc analysis with a small set of firms to uncover how they should invest in stage time reduction given our empirical results. The post hoc analysis highlights that some firms are likely overinvesting in stage time reductions and destroying market value.